(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
A new porcelaneous foraminifer, Cairoella tricamerata n. gen., n. sp., is here described from the lower Cenomanian of the Monte Cairo area near Cassino (Southern Latium, Italy). The new taxon is characterized by an early stage with triloculine to quinqueloculine coiling, followed by one or two whorls, each consisting of three or more tubular, curved, flattened and undivided chambers, with depressed sutures; it is ascribed to the superfamily Milioloidea, but the inferred attribution to the family Hauerinidae remains uncertain. In the type-locality its occurrence is restricted to the back-edge facies of the Latium-Abruzzi carbonate platform represented by fossiliferous grain-supported limestone rich in Sellialveolina viallii Colalongo, 1963.